The Role of Money Demand in a Business Cycle Model with Staggered Wage Contracts - Rafael Gerke; Jens Rubart (Technische Universität Darmstadt, Department of Law and Economics, 2005)
The question of the main determinants of persistent responses due to nominal shocks captures, at least since Chari et al. (2000), a major part of the recent macroeconomic debate. However, the question whether sticky wages and/or sticky prices are sufficient for persistent reactions of key economic variables remains open. In the present model we allow for nominal rigidities due to Taylor- like wage setting as well as price adjustment costs. However, as our analysis illustrates, smoothing marginal costs seems crucial to derive a contract multiplier, wage staggering alone is not sufficient. Without considering a more specific analysis of factor market frictions, we enforce a point made by Erceg (1997) by analyzing the structure of money demand. In particular, we analyze a ?standard? consumption based money demand function by varying the interest rate elasticity of money demand as well as the steady state rate of money holdings. Our results show that the persistency of the output/price dynamics can be affected crucially by the form of the implicit money demand function. In particular, it is shown that staggered wage contracts have to be accompanied by a sufficiently low interest rate elasticity, otherwise the model fails to reproduce reasonable responses of real variables.
Keywords: E41; E32; 330; Monetary Policy Shocks; Sticky Prices; Staggered Wages; Money Demand; Konjunkturtheorie; Lohnrigidität; Geldnachfrage; Theorie